2015
DOI: 10.1111/tbed.12333
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oral Bait Vaccine Efficacy Against Classical Swine Fever in Village Backyard Pig Farms in Bhutan

Abstract: Control and eradication of classical swine fever (CSF) in countries with a high proportion of backyard holdings is a challenge. Conventional attenuated Chinese C-strain vaccines, though safe and effective, are difficult to use in backyard farms due to various practical reasons. The aim of this study was to evaluate the efficacy of the CSF oral bait vaccine in village backyard pig farms and to assess the farmers' knowledge on CSF and motivation on using oral vaccines. The pigs were fed the bait by the farmers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…While failure due to poor technique cannot be discounted, false reporting of the vaccination status of an individual animal by farmers might cause these seemingly negative results in vaccinated animals. In another study, similar levels of seroconversion were reported when an injectable preparation of a Chinese vaccine strain was used (Malo 2011) or when oral preparations were used for village pigs (Milicevic et al 2013, Monger et al 2015. Further study is warranted to assess the efficacy of the Chinese vaccine strain in village pigs.…”
Section: Discussionmentioning
confidence: 71%
“…While failure due to poor technique cannot be discounted, false reporting of the vaccination status of an individual animal by farmers might cause these seemingly negative results in vaccinated animals. In another study, similar levels of seroconversion were reported when an injectable preparation of a Chinese vaccine strain was used (Malo 2011) or when oral preparations were used for village pigs (Milicevic et al 2013, Monger et al 2015. Further study is warranted to assess the efficacy of the Chinese vaccine strain in village pigs.…”
Section: Discussionmentioning
confidence: 71%
“…In addition, these vaccines were also adapted to a bait format for oral immunization of wild boar [6,215,216] and were recently explored for the vaccination of domestic pigs under backyard conditions [217,218,219]. While these vaccines usually have outstanding virtues in terms of onset, spectrum and duration of immunity [158,220,221,222,223], the main drawback is the lack of a serological marker concept [160] that would allow differentiation of field virus infected from vaccinated animals (DIVA concept).…”
Section: Vaccinationmentioning
confidence: 99%
“…The uptake of oral vaccine bait is one of the factors influencing the success rate of oral immunization (Monger et al, ). To ensure the success rate of vaccine uptake, different strategies were utilized, such as providing the vaccine along with banana or rice bran or administering directly hand to mouth (Porntrakulpipat et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The price of oral vaccine is relatively high compared to vaccines for parenteral application (Monger et al, ). This fact makes oral vaccines less attractive to the relevant authorities despite the fact that inefficient parenteral vaccination campaigns with the described constraints tend to fail to reach appropriate herd immunity and should therefore not be considered cost efficient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation